2002
DOI: 10.1021/bi0264723
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenesis by Acrolein-Derived Propanodeoxyguanosine Adducts in Human Cells

Abstract: Acrolein, which is widely spread in the environment and is produced by lipid peroxidation in cells, reacts with DNA to form two exocyclic 1,N2-propanodeoxyguanosine (PdG) adducts. To establish their relative contribution to the acrolein mutagenicity, the genotoxic properties of alpha-OH-PdG and gamma-OH-PdG together with their model DNA adduct, PdG, were studied in human cells. DNA adducts were incorporated site-specifically into a SV40/BK virus origin-based shuttle vector and replicated in xeroderma pigmentos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
142
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(153 citation statements)
references
References 26 publications
8
142
1
2
Order By: Relevance
“…The data reported here, together with the results of Feng et al demonstrating that it causes DNA damage at mutational hot spots in the p53 gene (3), suggest involvement. Furthermore, adduct 3 has been shown to be mutagenic in human cells, causing G to T transversions (17), and we have shown that this adduct is present in human lung (8). However, levels of adducts 3 and 4 in human lung were unrelated to smoking status in our study, although the number of subjects was small.…”
Section: Discussioncontrasting
confidence: 66%
“…The data reported here, together with the results of Feng et al demonstrating that it causes DNA damage at mutational hot spots in the p53 gene (3), suggest involvement. Furthermore, adduct 3 has been shown to be mutagenic in human cells, causing G to T transversions (17), and we have shown that this adduct is present in human lung (8). However, levels of adducts 3 and 4 in human lung were unrelated to smoking status in our study, although the number of subjects was small.…”
Section: Discussioncontrasting
confidence: 66%
“…Although it is a minor adduct, α-AcrdG is >10 times more mutagenic than γ-AcrdG. 37 Surprisingly, the signal Figure 3. The typical ESI-MS spectra of AcrdG isomers were obtained when different additives to the mobile phase were used.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Both isomeric adducts were shown to induce base substitutions with G→C transversions predominating. α-Hydroxy-PdG gave rise to a higher miscoding frequency when incorporated into DNA of human xeroderma pigmentosum A cells [86,87]. HydroxyPdG adducts have been detected in liver tissue DNA of humans and rodents without carcinogen treatment [88].…”
Section: Adduction Of Acrolein To Dnamentioning
confidence: 99%